Analisis Manajemen Assets George Washington University - Ismaul Rofi’ah; Kyuriyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Assets are a crucial component in supporting the operational sustainability and success of institutions, including higher education organizations. Effective asset management reflects financial efficiency and long-term institutional resilience. This study aims to analyze the components and development of assets at George Washington University (GWU) during the 2021–2023 period and to evaluate the effectiveness of GWU’s asset management in maintaining financial stability. The research employs a qualitative descriptive approach using a literature study (library research) method focusing on financial reports of GWU and relevant literature on higher education asset management. The analysis technique includes data reduction, data presentation, and conclusion drawing. The results show that GWU’s asset components consist of cash, accounts receivable, contributions receivable, investments, loans and notes receivable, property, plant and equipment, operating lease right of use assets, and other assets. Over the three-year period (2021–2023), GWU’s total assets experienced positive fluctuations with a steady increase in fixed assets and investments as the largest contributors. This indicates that GWU has successfully managed its assets productively, despite variations in current assets due to operational needs and global economic conditions. These findings imply that successful university asset management depends on maintaining an optimal balance between liquidity and long-term investment to ensure institutional sustainability.